AN OVERVIEW OF DEPRESSION TENDENCIES IN PATIENTS WITH TYPE 2 DIABETES MELLITUS IN KEBONSARI PRIMARY HEALTHCARE CENTER, SURABAYA CITY - Iftitah Shofiyati (Universitas Airlangga, 2020)
Type 2 diabetes mellitus (DM) occurs due to insufficient insulin production or insulin resistance in the human body. Type 2 DM also causes physical weakness, vision problems, risk of death, and depression. This study aimed to describe depression tendencies in patients with type 2 DM under treatment in Kebonsari Primary Healthcare Center, Surabaya city. This study was a descriptive study with a cross-sectional approach. The research samples were 74 people with type 2 DM in the Kebonsari Primary Healthcare Center, Surabaya city. These respondents selected using simple random sampling had met the inclusion criteria. These repsondents were aged more than 25 years old, did not experience psychological disorders, and had suffered from type 2 diabetes mellitus for 5 years. The data analysis was done using a univariate analysis by looking at the frequency distribution of variables. The results indicate that the prevalence of patients with type 2 DM who tended to experience depression was at 50%. The majority of patients with type 2 DM who experienced depression were women (47.4%) and elderly (aged 46-65 years) (41.9%). Most of them had low education levels (62.2%), and some respondents had complications (37.8%) and poor family support (62.2%). Support from closest people such as family support can improve the adaptation of patients with the disease and can prevent psychological disorders, especially depression in patients with type 2 DM. Keyword: type 2 diabetes mellitus, family support, depression tendencies.